A New Chemoenzymatic Synthesis of the Chiral Key Intermediate of the Antiepileptic Brivaracetam - Ciceri, Samuele (Molecules, 2018)
Brivaracetam is a new anticonvulsant compound, recently approved as an antiepileptic drug. This drug substance presents a 4-substituted pyrrolidone structure: the (4R)-configuration of the stereocenter present on the heterocyclic ring is the main target of the synthesis. The described method allows to prepare the suitable optically pure 2-substituted primary alcohol by means of a Pseudomonas fluorescens lipase-catalyzed transesterification. The obtained (2R)-alcohol was easily transformed into the (3R)-3-propylbutyrolactone, an advanced intermediate of brivaracetam. The described synthetic pathway is completed with the chromatographic methods and the NMR analyses necessary to establish the chemical and the optical purity of the intermediates and of the final lactone.